A Study of Shashi Deshpande's a Matter of Time: Exploring the human experience through three generations (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Deshpande'snovel A Matter of Time clearly shows, her concerns to concentrate on largerissues pertaining to human life and what is remarkable is that the novelistherself is not aware of it. She told her interviewer M.D. Riti: "I havenow reached a point.... at which I feel there must be change in my writing. Ido not know what kind of change this will be. One gets stale after awhile" (28). The novel deals with the human predicament of three womenrepresenting three generations of the same family. For the first time Deshpandemakes a man the protagonist of her novel, but this hasn't led her to focusentirely on the man.